Four South African “sunrises”, four cartoons, four eras and the cyclical nature of history (Historia, 2021)
History as having a cyclical nature has been accepted as theory since ancient times. According to this cyclical theory, events happen in recurring cycles, or, simply put, it is a matter of “history repeating itself”. This article examines four cartoons as an illustration of history as cyclical phenomenon in one metaphor that was used in four political cartoons that were published over just more than a century in South Africa. All four cartoons depict the metaphor of “a new dawn” or a “new sunrise”, although representing four different political eras in the country. As foundational point of departure, media history and media historiography is discussed, followed by cartoons and their development as editorial comment, after which follows a discussion of the use of metaphor in cartoons. The four cartoons, representing four political eras, are next presented, supplemented by brief biographies of the four cartoonists as further context. The cartoons, although representing different political eras in South Africa, are linked through the use of the sunrise metaphor, graphically illustrating history as being cyclical, or repeating itself. This article hopes to not only contribute to South African (media) history, but especially to stimulate cartoon studies, specifically from within a (media) historiographical framework.
Keywords: African nationalism; Afrikaner nationalism; cartoons; colonialism; imperialism; history; media history; South Africa